Eksistensi Suku Laut (Suku Akit) di Dusun Bangsal Ujung, Desa Sungai Asam, Kabupaten Tanjungbalai Karimun, Provinsi Kepulauan Riau - Marisa Elsera; Glory Yolanda Yahya; Elfa Oprasmani; Casiavera Casiavera; Syakila Syakila (Jurnal Sosiologi Andalas, 2021)
Suku Akit (suku laut) who originally lived as a nomadic person lives in sampan. They have occupied houses on the land. Their houses were obtained through the government program Ministry of Social Affairs. This study described the existence of Suku Akit. They have not only settled/ relocated but also experienced changes in economies such as switching of traditional fishing tools to aquaculture, learning in schools, believing in religion, and having a figure who can bridge of the Suku Akit